Changes in the reference lumen size of target lesions before and after coronary stent implantation: Evaluation with frequency domain optical coherence tomography. (1st September 2015) - Kurokawa, Muneo; Uemura, Shiro; Watanabe, Makoto; Dote, Yoko; Sugawara, Yu; Goryo, Yutaka; Ueda, Tomoya; Okayama, Satoshi; Kayashima, Michinori; Saito, Yoshihiko
Abstract: Objective: In optical coherence tomography (OCT)-guided percutaneous coronary intervention (PCI), stent size is usually determined according to the pre-PCI lumen size of either the distal or proximal reference site. However, the effect of the OCT imaging catheter crossing the target lesion on the reference lumen measurements has not been studied. We evaluated changes in the reference lumen size before and after PCI using frequency domain OCT. Methods: For 100 consecutive patients with PCI, mean lumen diameter (LD) and lumen area (LA) were measured at the proximal and distal reference sites before and after coronary stent implantation with OCT. Results: Mean LD and LA of the distal reference site were significantly increased after PCI with stent implantation (2.57 ± 0.6 to 2.62 ± 0.64 mm, p < 0.01 and 5.20 ± 2.66 to 5.41 ± 2.54 mm 2, p < 0.01, respectively). By contrast, these indices at the proximal reference site were significantly decreased. ROC curve analysis selected MLA of 1.50 mm 2 as the best cutoff value for changes in mean LD. Distal mean LD was markedly increased after PCI in lesions with MLA < 1.50 mm (2.28 ± 0.48 to 2.40 ± 0.17 mm, P < 0.001), but did not change in lesions with MLA > 1.50 mm 2 . Tissue characteristics were not correlated with changes in reference lumen size. Conclusions: When we select the stent size during OCT-guided PCI, we need to pay attention to the decrease in the luminal measurement of the reference sites, especially in lesions with tight stenosis.